Omnibus Law dan Lingkungan Yang Berkelanjutan: Perizinan Pendirian Perumahan dan Kawasan Pemukiman - Sarbini Sarbini; Ria Wierma Putri; Kasmawati Kasmawati; Daryanti Haidar (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The establishment of housing and residential areas is part of the governance system in the context of sustainable community life. This paper considers that every country has legal rules to realize the system and management of governance in the establishment of housing and residential areas through the Building Permit. However, in the Omnibus law, the IMB permit is simplified and/or abolished regarding environmental permits that were part of the issuance of IMB by the government in the previous regulation. In addition, licensing has at least 3 main functions, namely, first as an instrument in development planning, second as a financial function for the state, and third as a regulation in the actions and behavior of the community towards environmental permits to prevent environmental damage or pollution. So this research will limit the importance of legal instruments in an effort to regulate the governance of buildings erected in certain areas in order to create buildings that are safe and in accordance with land use in order to create a sustainable environment.